The Concept of Tawḥīd in the Thought of Haji Batin Sulaiman: A Study of the Manuscript Syair Tsani - Masrin, Suryan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This paper examines the concept of tawḥīd (Islamic monotheism) in the thought of Haji Batin Sulaiman as reflected in Syair Tsani, a poetic summary of Asrār al-Insān by Shaykh Nūr al-Dīn al-Rānīrī. As a local Muslim scholar, Haji Batin Sulaiman devoted great attention to issues of tawḥīd within a society still influenced by local traditions and syncretic elements. His theological ideas are expressed not only through oral preaching but also through a number of written works in Malay Jawi script. The findings indicate that Haji Batin Sulaiman’s conception of tawḥīd emphasizes the strengthening of faith through a synthesis of spiritual and Sufi dimensions. Consequently, his thought can be regarded as a valuable intellectual legacy and a source of inspiration for the development of Islamic education rooted in the values of tawḥīd.